O mundo nas mãos do adolescente: entre Apolo e Dioniso, entre o eros e o caos - Paula Mastroberti (Universidade de Brasília, 2010)
Based on the series Poderosa, by Sergio Klein (Sao Paulo: Fundamento), this work analyses the representation of the adolescent in the personage-heroine, Joana Dalva, who has the power of changing daily events by re-writing them. The study begins with the polarity Apollo/Dionysus, as conceived by Friedrich Nietzche. It begins to present the series within its graphic context showing how it contributes to an identification between text and reader; following the protagonist in a relation with the remaining narrative elements, reflecting about the way she uses her power and its meaning while metaphor of the psychic and body-sensual conflicts, caused by typical age changes. The work also includes a brief historical overview of youth, from the relations of his body with the collective or socio-cultural body, between the young individual body and the social body, which helps placing Klein’s piece in post-modernity and confirms it as a sign of an Apollonius vision of adolescence by contemporary society. To conclude, and based on reports obtained from a quick interview with some librarians from Porto Alegre and other cities in Rio Grande do Sul State, I place the Series in the literary system and try to discover the causes of its success among its young readers.